22‐3: Distinquished Student Paper: Flexible Quantum Dot Light Emitting Devices for Photomedicine. Issue 1 (30th May 2018) - Chen, Hao; Yeh, Tzu-Hung; He, Juan; Zhang, Caicai; Abbel, Robert; Lanzafame, Raymond; Stadler, Istvan; Celli, Jonathan; Liu, Shun-Wei; Wu, Shin-Tson; Dong, Yajie
Abstract : We demonstrate highly efficient quantum dots with narrow spectra and specific peak wavelengths for photomedical applications. Flexible quantum dot light emitting devices with peak EQE of 8.2% and luminance over 20, 000 Cd/m 2 were achieved which will be employed for treatment of oral cancers or diabetic wounds.